High genetic diversity of human immunodeficiency virus type 1 in Angola - Bartolo, I (2015)
To investigate which HIV-1 genetic forms are circulating in Angola, we have determined the gag and/or env genotypes of 48 isolates from patients living in Cabinda and Luanda provinces. The following subtypes were identified: A(1) (18 samples, 38%), C (7,